Laser frequency stabilisation onto a high-finesse optical cavity - Jernstedt, Alex (My University, 2026)
Laser cooling of strontium requires repump lasers to maintain an atom population in states accessible to the cooling cycle. This work presents the development of an experimental setup for frequency stabilisation of two repump lasers at 679 and 707 nm using a high-finesse optical cavity. The method utilises the Pound-Drever-Hall (PDH) technique to produce error signals. Coupling of the 707 nm laser to the cavity is demonstrated with a mode-matching efficiency of 40%. Phase modulation using an electro-optic modulator (EOM) is generated and detected, enabling the production of PDH error signals. While these signals have not yet been used to lock the lasers, the setup provides a foundation for future implementation of cavity-stabilised repump lasers.